Pengembangan Kelompok Ternak Mandiri Hijauan Pakan Berbasis Pengelolaan Lahan Marginal di Desa Duwet, Wonosari, Gunungkidul - Miftahush Shirothul Haq; Aji Praba Baskara; Aqmal Nur Jihad; Fathi Alfinur Rizqi; Novat Pugo Sambodo; Sri Andayani (Direktorat Pengabdian kepada Masyarakat, 2026)
Gunungkidul Regency is a karst region that is vulnerable to drought due to the low ability of the soil to retain water. This has a significant impact on the provision of forage for the livestock sector. This community service aims to improve animal feed independence through the application of irrigation technology and legume plant integrity in marginal land in Duwet Village, using the Participatory Rural Appraisal (PRA) approach method which is divided into 4 (four) stages: Planning, Organizing, Actuating, and Controlling (POAC). This activity includes field surveys, socialization, initial assessment, participatory installation, as well as technical assistance and ongoing monitoring. After 8 (eight) harvests, the application of sprinkler irrigation was able to increase and stabilize forage productivity in the range of 16-17 kg/m2. The integration of legume plants contributes to improving soil fertility through nitrogen fixation, this is what supports the sustainable growth of forage crops. Total forage production varied between locations, ranging from 0.40 to 1.57 tonnes, indicating the influence of specific factors such as soil conditions, water availability, and farming management. The program also demonstrated success in increasing the capacity and participation of livestock groups, as evidenced by the high level of involvement in system installation and management. Operational costs, technology maintenance, and the need for a more adaptive approach to local conditions are challenges faced in this activity. However, overall, the program is quite effective in supporting livestock feed security and reducing dependence on traditional patterns, and has the potential to be replicated with adjustments based on regional characteristics.